Monkeypox’s Multisectoral Challenge: Why One Health is the key? - Ranakoti, Neeraj; Singh, Meenu; Naithani, Priyanka; Silswal, Diksha; Singh, Mahendra (Indian Journal of Community Health, 2025)
The global emergence of mpox (Monkeypox), a zoonotic disease attributed to the monkeypox virus (MPXV), presents a considerable public health dilemma, particularly in the context of the ongoing ramifications of the COVID-19 pandemic. This pathogen, which originated in Central and West Africa and was first documented in human cases in 1970, has proliferated internationally, with the outbreak in 2022 prompting the World Health Organization (WHO) to classify it as a Public Health Emergency of International Concern. The epidemiological profile of mpox indicates notable variations in its distribution, with elevated incidence rates particularly observed among male demographics, notably within the gay, bisexual, and other men who have sex with men (MSM) communities. The primary mode of transmission is through direct exposure to infected biological fluids, lesions, or mucous membranes, while environmental reservoirs and potential vertical transmission are considered to play a lesser role. Populations deemed vulnerable, including those with immunocompromised states and individuals situated in socioeconomically disadvantaged environments, experience increased susceptibility. Clinical features, such as lymphadenopathy, serve to distinguish mpox from smallpox. Diagnostic techniques, including polymerase chain reaction (PCR) and advanced deep learning models, provide high levels of accuracy, although rapid antigen testing remains inconsistent in reliability. Current therapeutic interventions encompass tecovirimat, cidofovir, and brincidofovir, with tecovirimat demonstrating the most substantial efficacy. Severe cases necessitating hospitalization may arise due to complications such as proctitis, secondary infections, or conditions like encephalitis. Adopting a One Health framework, which amalgamates human, animal, and environmental health considerations, is imperative for the timely detection, surveillance, and management of prospective outbreaks. Collaborative initiatives and technological advancements, such as Geographic Information Systems (GIS), are crucial in refining response strategies and achieving enduring public health objectives.